Pesan Perdamaian dalam Video Klip Atouna El Toufoule: Analisis Semiotik Charles Sanders Peirce - Arin Faridatul Azma (Al-Ma‘rifah, 2021)
The purpose of this article is to find out the description of peace messages in the Atouna El Toufoule video clip. In the video clip of Atouna El Toufoule, several signs have meaning. The study of meaning in this article uses a qualitative research methodology by analyzing images as data which is analyzed using Charles Sanders Peirce’s semiotics in finding meaning through signs, objects, and interpretants. The results of this study indicate that sign is mostly motivated by social context and does not require excessive interpretation of meaning. The object takes the side of social life that occurs in Palestinian society. Interpretants also sometimes directly criticize social life, culture, and the environment around them. The video clip of Atouna El Toufoule contains a moral message and an invitation to create peace for children living in conflict areas. They need a vacation so they can feel peace and freedom in their lives.